Case report: two cases of rhabdomyolysis following esketamine treatment - Zeiss, René; Schweizer, Melissa; Connemann, Bernhard; Malejko, Kathrin (Frontiers in Psychiatry, 2024)
Major depressive disorder is a mental disorder affecting millions of people worldwide. A considerable proportion of patients demonstrate a lack of response to conventional treatment. With the recent introduction of esketamine, a new treatment option has been approved for treatment-resistant depression. Although the medication is efficacious in a substantial portion of cases, rare, but possibly serious, adverse effects may occur. This case series shows two cases of rhabdomyolysis, a destruction of muscle tissue with elevated creatine kinase levels, after administration of esketamine. The first case presented is about a 33 year old male patient who suffered from a severe episode of a depressive disorder. He got nasal esketamine as an emergency treatment. While there was an initial improvement regarding the depressive symptoms, the patient developed muscle pain and fatigue after the administration of the fourth dose, with creatine kinase (CK) levels above 22,000 U/L, indicating rhabdomyolysis. Following the discontinuation of esketamine and the implementation of supportive care, the CK levels returned to normal and the depressive symptoms abated. The second case is about a 22-year-old male patient who also suffered from a severe depressive episode and got eketamine as an emergency treatment. Following the tenth dose, the patient exhibited muscle weakness and elevated CK levels (8,032 U/L), which persisted even after dose reduction. Esketamine administration was stopped, and the following monitoring demonstrated a slow return to normal levels of CK and liver enzymes. In both cases, there was no known medical history and both patients developed rhabdomyolysis after administration of esketamine. The temporal connection suggests a possible causal relationship. We found no literature on esketamine-induced rhabdomyolysis following the administration of nasal esketamine. However, these two cases emphasize the need of monitoring for laboratory changes like elevated CK-levels in patients receiving esketamine, especially considering its growing use in treatment-resistant depression.